2020
DOI: 10.3390/pathogens9110933
|View full text |Cite
|
Sign up to set email alerts
|

Update and New Epidemiological Aspects about Grapevine Yellows in Chile

Abstract: To date, phytoplasmas belonging to six ribosomal subgroups have been detected to infect grapevines in Chile in 36 percent of the sampled plants. A new survey on the presence of grapevine yellows was carried out from 2016 to 2020, and 330 grapevine plants from the most important wine regions of the country were sampled and analyzed by nested PCR/RFLP analyses. Phytoplasmas enclosed in subgroups 16SrIII-J and 16SrVII-A were identified with infection rates of 17% and 2%, respectively. The vineyards in which the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The detection of 16SrIII‐J in symptomatic faba bean samples is the first identification of phytoplasmas enclosed in this ribosomal subgroup in Peru; they were reported first in Brazil (Montano et al., 2000) and later infecting several other crop species in South American states such as Argentina (Fernández et al., 2020; Galdeano et al., 2013), Brazil (Munhoz et al., 2019) and Chile (Quiroga et al., 2020). The identification of variability at the 16Sr level is not unusual in phytoplasmas classified in the 16SrIII group where the frequent presence of interoperon heterogeneity is reported in several strains (Davis et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of 16SrIII‐J in symptomatic faba bean samples is the first identification of phytoplasmas enclosed in this ribosomal subgroup in Peru; they were reported first in Brazil (Montano et al., 2000) and later infecting several other crop species in South American states such as Argentina (Fernández et al., 2020; Galdeano et al., 2013), Brazil (Munhoz et al., 2019) and Chile (Quiroga et al., 2020). The identification of variability at the 16Sr level is not unusual in phytoplasmas classified in the 16SrIII group where the frequent presence of interoperon heterogeneity is reported in several strains (Davis et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Insect vectors can, therefore, sporadically visit crops and transmit phytoplasmas, suggesting that spontaneous vegetation may also be a reservoir for these phytoplasmas [29,44,45]. This situation has been evidenced in epidemiological studies associated with grapevine yellows in Chile [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were transported in thermoregulated containers and stored at 4 • C before nucleic acid extraction. DNA was extracted from 1 g of midribs using the CTAB method [48]. The nucleic acids were dissolved in Tris-EDTA buffer pH 8.0 and kept at 4 • C. All samples were analyzed by PCR and nested-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…P. asteris' is widely reported to infect corn on the American continent (Lee et al, 2004), this is the first detection of 16SrIII-J phytoplasmas in corn. The 16SrIII-J phytoplasma strain is widespread in other countries of South America such as Brazil (Montano et al, 2000), Argentina (Galdeano et al, 2013) and Chile (Quiroga et al, 2020) where it was detected in several herbaceous and woody horticultural species. Recently it was also identified in faba bean in Peru (Torres-Suarez et al, 2021) and insect vectors of this phytoplasma strain were identified as Paratanus exitiosus (Beamer) and Bergallia valdiviana Berg 1881 in Chile (Quiroga et al, 2019).…”
Section: Discussionmentioning
confidence: 99%